Investigate the liberation of copper from waste Printed Circuit Boards (PCBs) - Mohd Zaheruddin, Kasmuin; Aimi Noorliyana, H.; Md. Fazlul, Bari; Sri Asliza, Md. Amin; Faizul, Che Pa; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.